Synovial chondromatosis of the temporomandibular joint with extension into the middle cranial fossa and internal carotid canal. Issue 7 (July 2017) - McCaffery, C.; Dodd, M.; Bekiroglu, F.; Twohig, E.
Abstract: This report presents the case of an extensive synovial chondromatosis of the temporomandibular joint (TMJ), with extension into the middle cranial fossa, middle ear, and carotid canal. Synovial chondromatosis of the TMJ is rare, particularly when associated with intracranial involvement. This case is unique owing to its size and the involvement with the internal carotid artery. The importance of a multidisciplinary approach in the surgical management of such a rare and complex form of this condition is highlighted.